Influence of mycorrhizal fungi on seed germination and growth in terrestrial and epiphytic orchids - Alghamdi, Sameera A. (Saudi J Biol Sci, 2019)
Epiphytes constitute over 70% of orchid diversity, but little is known about the functioning of their mycorrhizal associations. Terrestrial orchid seeds germinate symbiotically in soil and leaf litter, whereas epiphytic orchids may be exposed to relatively high light levels from an early stage of development and often produce green seeds. This suggests that seedlings of the two groups of orchids may differ in their responses to light and requirements for mycorrhiza-supplied carbon. The interactive effects of light, exogenous carbon and mycorrhizal status on germination and growth were investigated in vitro using axenic agar microcosms for one tropical epiphyte and three geophytic orchid species. The geophytic species strongly depended on their mycorrhiza for growth and this could not be substituted by exogenous sucrose, whereas the epiphytic species achieved 95% of the mycorrhizal seedling volume when supplied with exogenous sucrose in the dark. Mycorrhiza status strongly interacted with light exposure, enabling germination. Light inhibited or severely reduced growth, especially for the terrestrial orchids in the absence of mycorrhiza. For the first time, this study showed the parallel ecological importance of mycorrhizal fungi in overcoming light inhibition of seed germination and growth in both terrestrial and epiphytic orchids.